2012
DOI: 10.1007/s00484-012-0533-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermographic evaluation of climatic conditions on lambs from different genetic groups

Abstract: In production systems the characterization of genetic resources in relation to their capacity to respond to environmental conditions is necessary. The objective of this study was to evaluate the use of infrared thermography for separation of animals from different genetic groups and determine which phenotypic traits are important for climatic adaptation. A total of 126 suckling lambs from four different genetic groups (Santa Inês--SI, Bergamasca--B, Bergamasca X Santa Inês--BS, and Ile de France X Santa Inês--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 18 publications
3
9
1
1
Order By: Relevance
“…In this study, high THI was observed in the afternoon, reaching values classified as danger and emergency [17]. This high amplitude of thermal variation observed in the present study have already been reported in the Midwest region of Brazil, where animals tend to suffer from cold stress at night and heat stress during the day [19]. The animal’s ability to respond to heat stress depends upon exposure to low temperatures during the night, and more specifically, the duration and intensity of this low temperature [9].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In this study, high THI was observed in the afternoon, reaching values classified as danger and emergency [17]. This high amplitude of thermal variation observed in the present study have already been reported in the Midwest region of Brazil, where animals tend to suffer from cold stress at night and heat stress during the day [19]. The animal’s ability to respond to heat stress depends upon exposure to low temperatures during the night, and more specifically, the duration and intensity of this low temperature [9].…”
Section: Discussionsupporting
confidence: 81%
“…Infrared thermography has been shown to be related to several physiological processes associated with heat tolerance [19,29]. In the present study, the thermographic temperatures of the several body areas measured using an infrared camera were affected by period of the day and, as expected, were lower in the morning period with cooler environmental temperatures.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Alternatively, environmental parameters could be bypassed entirely in favour of measuring the body temperature of animals-after all, this factor is a direct cause of thermal stress. Contact thermometers, infrared thermometers, and thermal lamps are all potential methods [10,14,15]; however, these types of measurements are challenging, expensive, and difficult to automate.…”
Section: Introductionmentioning
confidence: 99%